Development of a smart garment to reduce kyphosis during daily living. - Lou E; Lam GC; Hill DL; Wong MS; Lou, Edmond; Lam, Gabrielle C; Hill, Douglas L; Wong, M S (Medical & Biological Engineering & Computing, 2012)
Many of the aches and pains of adults are the result of the long-term effects of bad posture or body misalignment. Postural kyphosis in adolescence, which is an excessive rounding of the upper spine, may be one of the effects of poor standing and sitting habits. A smart garment, consisting of a harness and two data-sensor loggers, was developed to monitor and provide vibration feedback to wearers to improve their posture during daily activities. Laboratory tests verified that the garment could provide an accuracy of 2 ± 2° during static measurement and 3 ± 2° during stable or slowly changing posture activities and 4 ± 4° during rapidly changing posture activities. Four volunteers wore the system for 3 h per day and for 4 consecutive days. The feedback was provided on the last 2 days and the kyphotic angle reduced by 8 ± 1° and 8 ± 2° on the last 2 days, respectively. Although the long-term effects of reminding the subjects' posture is still not clear, a short-term result shows promise that the smart garment may be able to improve the kyphosis.